2022
DOI: 10.1039/d2cc02272a
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic activity for proton reduction by a covalent non-metal graphene–fullerene hybrid

Abstract: A metal-free electrocatalyst consisting of a covalently linked graphene–fullerene hybrid material was prepared following the chemistry of fluorographene, displaying improved hydrogen evolution reaction electrocatalytic activity and high durability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…One promising approach involves harnessing the unique properties of C 60 and derivatives, incorporating them into catalytic materials, and thereby enhancing their electrocatalytic performance. [120,121] For example, considering membrane-based alkaline electrolysis represents a cost-effective and environmentally friendly approach to hydrogen production, Chen et al [3] suc-cessfully employed an enhanced LLIP method to create C 60 bulk crystals, which were subsequently utilized for the synthesis of thin layers of Pt/C 60 nanosheets (Figure 13a). Atomic Force Microscopy analysis confirmed that the Pt/C 60 nanosheets exhibited a size distribution ranging from 200 to 1000 nm while maintaining a uniform thickness of ≈5 nm.…”
Section: Hermentioning
confidence: 99%
“…One promising approach involves harnessing the unique properties of C 60 and derivatives, incorporating them into catalytic materials, and thereby enhancing their electrocatalytic performance. [120,121] For example, considering membrane-based alkaline electrolysis represents a cost-effective and environmentally friendly approach to hydrogen production, Chen et al [3] suc-cessfully employed an enhanced LLIP method to create C 60 bulk crystals, which were subsequently utilized for the synthesis of thin layers of Pt/C 60 nanosheets (Figure 13a). Atomic Force Microscopy analysis confirmed that the Pt/C 60 nanosheets exhibited a size distribution ranging from 200 to 1000 nm while maintaining a uniform thickness of ≈5 nm.…”
Section: Hermentioning
confidence: 99%